2018
DOI: 10.3390/su10082953
|View full text |Cite
|
Sign up to set email alerts
|

How Far Has China’s Urbanization Gone?

Abstract: China's rapid urbanization has attracted wide international attention. However, it may not be sustainable. In order to assess it objectively and put forward recommendations for future development, this paper first develops a four-dimensional Urbanization Quality Index using weights calculated by the Deviation Maximization Method for a comprehensive assessment and then reveals the spatial association of China's urbanization by Exploratory Spatial Data Analysis. The study leads to three major findings. First, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…During this period, the emergence of bipolar membranes, leading to new and different applications where pH differences play a major role (production of acids and bases, recovery of organic acids), the growing importance of resource recovery and related selective recovery of anions and metals, and the design of alternative electrodialysis stack configurations, which are intended for selective separation in a series of applications [ 4 ], in parallel with an increase in population and urbanization of the Asia-Pacific region accelerated the needs for electrodialytic systems. As an example, China experienced a very significant boom in its urbanization from the 1990s with the rise of the Chinese economy [ 15 , 16 , 17 ]. Hence, between the beginnings of the country’s opening to a market economy in 1978 and 2013, the Chinese urban population increased more than fourfold, from 172 to 731 million people.…”
Section: Overview Of Electrodialytic Equipment Market and Manufactmentioning
confidence: 99%
“…During this period, the emergence of bipolar membranes, leading to new and different applications where pH differences play a major role (production of acids and bases, recovery of organic acids), the growing importance of resource recovery and related selective recovery of anions and metals, and the design of alternative electrodialysis stack configurations, which are intended for selective separation in a series of applications [ 4 ], in parallel with an increase in population and urbanization of the Asia-Pacific region accelerated the needs for electrodialytic systems. As an example, China experienced a very significant boom in its urbanization from the 1990s with the rise of the Chinese economy [ 15 , 16 , 17 ]. Hence, between the beginnings of the country’s opening to a market economy in 1978 and 2013, the Chinese urban population increased more than fourfold, from 172 to 731 million people.…”
Section: Overview Of Electrodialytic Equipment Market and Manufactmentioning
confidence: 99%
“…The results of analysis in this study pointed to the conclusion that urbanization quality, as well as the coupling coordination degree of five dimensions, was getting better and better during 2005-2015. However, despite the continuous improvement of urbanization quality in China [90], China's urbanization is still in a relatively low level of sustainability [91]. In 2015, only Beijing, Tianjin, Shanghai, and Zhejiang were in the high-quality grade of comprehensive urbanization, while no region was in the satisfactory grade, and most regions were in the medium-quality grade.…”
Section: Discussionmentioning
confidence: 99%
“…What we now face in China is the contradiction between unbalanced and inadequate development and the people's ever-growing needs for a better life. Disparity between the east and the west remains a major issue for China to address [90]. In brief, there was still a long way to go to realize the comprehensive improvement of urbanization in China.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid rise in urbanization and infrastructures can create several problems for the agriculture sector because peoples have started to convert their arable lands into commercial and residential areas. Xiao et al [9] concluded that if we take China as an example, the rise of urbanization and infrastructure development in China is increased very fast compared to other countries of the world. However, the share of the urban population is increased from 21.1% to 58.5% over the period 1982-2017 [10][11][12][13] .…”
Section: Introduction mentioning
confidence: 99%